Wild Edible Plants (WEPs): A Review on Their Importance, Possible Threats, and Conservation - Shirsat, Rupali; Koche, Dipak (Contemporary Research and Perspectives in Biological Science Vol. 2, 2024)
This chapter aims to present the current status of Wild Edible Plants (WEPs), highlight their importance as a nutrient source for future food security, explore the ethnic knowledge associated with them, identify the threats they face, and propose sustainable management strategies. The knowledge of Wild Edible Plants (WEPs) dates back to the dawn of human civilization. Today, they continue to play a crucial supplementary role in global food security. WEPs are integral to traditional food systems, offering nutritional and cultural value in daily life. They are increasingly recognized as a potential source of a naturally healthy diet. However, many WEP resources are under threat from various factors, including overexploitation, overgrazing, forest fires, agricultural encroachment, and the adverse effects of climate change. Consequently, there is an urgent need to conserve the diversity of WEPs and ensure their sustainable management. The conservation and sustainable management of wild edible plants (WEPs) are critical for ensuring future food security and maintaining ecological balance. By collaborating with indigenous and local communities, integrating traditional and scientific knowledge, and implementing comprehensive conservation strategies, we can safeguard the diversity of WEPs.